KEMISKINAN DAN PENGUASAAN TANAH DI PERDESAAN: ANALISIS TERHADAP SISTEM KEPEMILIKAN TANAH PERTANIAN DI DESA ROWOSARI KABUPATEN JEMBER - Ardiansyah (Al'Adalah, 2017)
This paper attempts to analyze the system of control of agricultural land in Rowosari Jember Village, how it affects the conditions of poverty of most of the people, and reads where the direction of life of the people is moving. Detailed and intensive data concerning agricultural land will be possible if the scope of the study is limited. West Hamlet Sawah Rowosari Village was chosen as the location of intensive research through spatial and social map-ping techniques to obtain a more comprehensive picture of the land tenure system and the social conditions of the West Sawah community. By mapping and analyzing the system of control of agricultural land in the village, the availability of employment opportunities outside agriculture, the tendency in which direction social movements in the village will be seen. Will they be forced to leave the village and move to the city as a result of the rationalization and mechanization of agriculture that may occur in the future or can they start a new life with hope while getting jobs in new industries that might be created in the village?